Innovation, startups and intellectual property management : strategies and evidence from Latin American and other regions - Leon, Ignacio de; Fernandez Donoso, Jose (Springer, 2017)
This book identifies the potential of intellectual property as a competitive asset for Latin American firms. The authors employ a cognitive approach that involves identifying why small firms are reluctant to register patents, resorting rather to alternative IP competitive strategies. This, in turn, results in the undercapitalization of intellectual assets, thus creating hurdles for the development of capital venture markets. Using new data gathered from highly innovative SMEs in Latin America and the Caribbean, the authors bring a fresh cognitive approach towards understanding the institutional role of intellectual property, and outline various new policy recommendations.